Roads and Diversification of Activities in Rural Areas: A Cameroon Case Study. (May 2015) - Castaing Gachassin, Marie; Najman, Boris; Raballand, Gaël
<x xml:space="preserve">Abstract</x> This article uses the 2001 Cameroon National Household Survey (ECAM II) to analyse how road access affects labour activities. It shows that one‐size‐fits‐all road investments are irrelevant because the effects of roads are neither systematic nor uniform: the impacts of isolation on household well‐being through labour‐market opportunities are heterogeneous and depend on local characteristics. In view of the diversification of activities in household strategy, it finds that better road access increases the number of activities within those households that are most isolated.